A study on the hemocompatibility of dendronized chitosan derivatives in red blood cells - Zhou YF; Li JM; Lu F; Deng JJ; Zhang JH; Fang PJ; Peng XS; Zhou SF (Dove Medical Press, 2015)
Yanfang Zhou,1,* Jiemei Li,1,* Fang Lu,1 Junjie Deng,2 Jiahua Zhang,1 Peijie Fang,1 Xinsheng Peng,1 Shu-Feng Zhou3 1Guangdong Medical Universtity, Dongguan, Guangdong, People’s Republic of China; 2Department of Materials Science and Engineering, Drexel University, Philadelphia, PA, USA; 3Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA *These authors contributed equally to this work Abstract: Dendrimers are hyperbranched macromolecules with well-defined topological structures and multivalent functionalization sites, but they may cause cytotoxicity due to the presence of cationic charge. Recently, we have introduced alkyne-terminated poly(amidoamine) (PAMAM) dendrons of different generations (G=2,3) into chitosan to obtain dendronized chitosan derivatives [Cs-g-PAMAM (G=2,3)], which exhibited a better water solubility and enhanced plasmid DNA transfection efficiency. In this study, we attempted to examine the impact of Cs-g-PAMAM (G=2,3) at different concentrations (25 µg/mL, 50 µg/mL, and 100 µg/mL) on the morphology, surface structure, and viability of rat red blood cells (RBCs). The results showed that treatment of RBCs with Cs-g-PAMAM (G=2,3) at 50 µg/mL and 100 µg/mL induced a slightly higher hemolysis than Cs, and Cs-g-PAMAM (G=3) caused a slightly higher hemolysis than Cs-g-PAMAM (G=2), but all values were <5.0%. Optical microscopic and atomic force microscopic examinations indicated that Cs-g-PAMAM (G=2,3) caused slight RBC aggregation and lysis. Treatment of RBCs with 100 µg/mL Cs-g-PAMAM (G=3) induced echinocytic transformation, and RBCs displayed characteristic irregular contour due to the folding of the periphery. Drephanocyte-like RBCs were observed when treated with 100 µg/mL Cs-g-PAMAM (G=3). Erythrocytes underwent similar shape transition upon treatment with Cs-g-PAMAM (G=2) or Cs. The roughness values (Rms) of RBCs incubated with Cs-g-PAMAM (G=2,3) were significantly larger than those for RBCs incubated with physiological saline (P<0.01), but the Rms showed no difference for Cs and Cs-g-PAMAM (G=2,3) (P>0.05). Furthermore, Cs-g-PAMAM (G=2,3) exhibited a lower cytotoxicity in human kidney 293T cells. These results indicate that Cs-g-PAMAM (G=2,3) are hemocompatible but may disturb membrane and lipid structures at higher concentrations. Further safety and biocompatibility evaluations are warranted for Cs-g-PAMAM. Our findings prove helpful for a better understanding of the advantages of combining PAMAM dendrimers and chitosan to design and develop new, safe, and effective drug delivery vehicles. Keywords: dendronized chitosan derivative, PAMAM, RBC, hemolysis, hemocompatibility